Theoretical calculation of self-propagating high-temperature synthesis (SHS) preparation of AlB12 - Chao Wang; Xiaoming Cao; Mengge Dong; Lu Zhang; Jianxing Liu; Xiaozhou Cao; Xiangxin Xue (Annals of Mathematics and Physics - Peertechz Publications, 2021)
Although experimental results of preparing AlB12 by self-propagating high-temperature synthesis using Mg-B2O3-Al2O3 as raw material has been studied, the theoretical calculations for the preparation of AlB12 have not been examined as thoroughly. In this article, for the first time, we report on the study of theoretical calculation and the adiabatic temperature, calculated, and compared with the actual reaction temperature. The Gibbs free energy for each level of reaction is also calculated. The calculation results show that the adiabatic temperature is 2789.5 K, the standard Gibbs free energy of each reaction is less than 0, and the reaction can proceed spontaneously, which is consistent with the results of the experiment.